Faktor-faktor yang Menentukan Eksistensi Kampung Pekojan sebagai Kampung Kota di Kota Semarang - Wahjoerini, Wahjoerini; Setioko, Bambang (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2014)
The existence of the urban kampong are the ability to maintain the morphology, functions and values in it. Trancik (1986) which says that the physical city space theory consists of figure ground, linkage, place. Kampong Pekojan is still the original building until recently. Kampong Pekojan still serves as a place of settlement, is still inhabited by the community. The purpose of doing research to find out what factors are determining the existence of the Kampung Pekojan as a urban kampong in Semarang from the physical aspect. The research method used was quantitative deductive rationalistic. From the results of the analysis using SPSS 16, had 3 factors which determine the existence of kampung Pekojan as urban kampong from the physical aspect is 1). Architectural of urban kampong factor 2) structure of urban kampong and 3). Elements and interaction space factors. The factors that most influence factor is the highest percentage with Architecture (32,477). These findings support the grand theory that States that the factors which determine the existence of urban kampong influenced by physical factors. However it was found that in the Kampung Pekojan, physical factors which affect more caused by factors of architecture.